2018
DOI: 10.3390/s18092852
|View full text |Cite
|
Sign up to set email alerts
|

An Intelligent Computing Method for Contact Plan Design in the Multi-Layer Spatial Node-Based Internet of Things

Abstract: Computational Intelligence (CI) has been addressed as a great challenge in recent years, particularly the aspects of routing, task scheduling, and other high-complexity issues. Especially for the Contact Plan Design (CPD) that schedules contacts in dynamic and resource-constrained networks, a suitable CI algorithm can be exchanged for a high-quality Contact Plan (CP) with the appropriate computational overhead. Previous works on CPD mainly focused on the optimization of satellite network connectivity, but most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Its outstanding feature is that all things will have the function of context perception, with stronger computing power and perception ability [5]. By integrating people and information into the Internet, the network will have billions or even trillions of connection nodes [6]. The IoE is based on the physical network, which increases the network intelligence and realizes the functions of integration, collaboration [7] and visualization between ''everything'' of the Internet.…”
Section: A Review On the Evolution Of Ioementioning
confidence: 99%
“…Its outstanding feature is that all things will have the function of context perception, with stronger computing power and perception ability [5]. By integrating people and information into the Internet, the network will have billions or even trillions of connection nodes [6]. The IoE is based on the physical network, which increases the network intelligence and realizes the functions of integration, collaboration [7] and visualization between ''everything'' of the Internet.…”
Section: A Review On the Evolution Of Ioementioning
confidence: 99%
“…The experiment showed that the algorithm has better congestion handling ability under high-traffic conditions than for other conditions. With the continuous improvements in the routing strategies of ground-based wireless networks, intelligent optimization algorithms such as the bee colony algorithm, ant colony algorithm and particle swarm algorithm have been extended to topological optimization and routing decision making for satellite networks in recent years [8][9][10]. Reference [30] verified the application value of the ant colony algorithm in single-layer NGEO.…”
Section: Related Workmentioning
confidence: 99%
“…However, if the head-wolf satellite odor is the highest in a local area, the routing algorithm will not be adjusted. Moreover, if calculating the concentration, it is necessary to eliminate the poor-wolf satellites according to formula (10). The purpose of the above operation is to eliminate the satellite nodes that do not meet the QoS guarantee requirements under the specific link queue length; this process is similar to pheromone release along the worst path in the improved ant colony algorithm.…”
Section: ) Detected-wolf Satellite and Its Behaviormentioning
confidence: 99%
See 1 more Smart Citation